The Effects of Employee Retention on Company Performance Results: the Mediating Role of HRM Outcomes in Central European Headquarters of MNCs - Haromszeki, Łukasz (Wpływ retencji pracowników na wyniki działalności firmy: Mediacyjna rola wyników ZZL w centralach korporacji międzynarodowych w Europie Środkowej, 2025)
Aim: The main goal of the article was to determine the mediating role of HRM outcomes in the relationships between employee retention (ER) and company performance results (CPR), and to establish the existence of any identifiable regularities in this scope in the pre-pandemic and pandemic period of COVID-19 (understood as a crisis condition) in the headquarters (HQs) of multinational companies (MNCs). Methodology: The empirical research was conducted in 200 MNCs with headquarters in Central Europe. To accurately reflect the relationships among the studied variables, the raw data were modified using the Efficiency Index (EI). The research hypotheses were tested and the mediating effects evaluated using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results: The study results indicate that HRM outcomes give a positive effect as a mediator between employee retention and company performance results in crisis. It shows statistically significant relations between business strategies, ER practices and companies performance results which can be useful for academic discourse and business decisions to plan the role of HRM for future crises. Implications and recommendations: The author’s own research revealed the mediation of HRM outcomes between ER and company performance results in finance, innovativeness, and quality. Thereby, this study has become another voice in the discussion on HRM strategies and policies for crisis taking into account four types of companies’ performance results. Originality/value: The research findings are not only of an innovative character due to MNCs being headquartered in Central Europe, but also because they link ER with companies results by using HRM outcomes and show its role in their performance and resilience in crisis.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 2, s. 50-63